Simulation of Geomagnetically Induced Currents in a Low‐Latitude 500 kV Power Network During a Solar Superstorm - J. J. Zhang; Y. Q. Yu; W. Q. Chen; C. Wang; Y. D. Liu; C. M. Liu; L. G. Liu (Space Weather)
Abstract Geomagnetically induced currents (GICs) are one of the main manifestations through which space weather affects human technical facilities, and GICs constitute the final link in the solar wind‐magnetosphere‐ionosphere‐ground interaction chain. Therefore, understanding the responses of power grids to solar superstorms is crucial for space weather research and emergency preparedness purposes. In this work, we combine the Space Weather Modeling Framework with a ground conductivity model and a model of the Chinese Guangdong 500 kV power grid to investigate the response of the whole power grid if the 23 July 2012 solar superstorm had struck the Earth. The maximum |GICs| produced in the power grid by this event reach approximately 400 A, which is more than thrice those measured during a strong magnetic storm with Kp = 8. Based on statistical analyses of the strength and duration of large GICs at 54 substations and a comparison with the GICs responsible for the Hydro‐Québec power outage on 13 March 1989, we stipulate that the risk of GICs in the Guangdong 500 kV power grid is very high. The simulation results also reveal that field‐aligned currents can play an important role in producing GICs in middle‐ and low‐latitude power grids during solar superstorms. This finding provides crucial insight for understanding the factors that generate strong GICs at middle and low latitudes.